Channel estimation for hybrid intelligent reflecting surface structure assisted mmWave communications - Youhua FU; Dong CHEN (Tongxin xuebao)
When adding intelligent reflecting surface (IRS) for assist communication in millimeter wave communication, the system becomes complicated and difficult to obtain channel state information (CSI).To solve these challenges, a hybrid intelligent reflecting surface structure was adopted, that is, the IRS was composed of a large number of passive elements and the limited radio frequency (RF) chains, where the limited RF chains were used to estimate the channel between the base station/terminal and the IRS.Based on the structure, a channel estimation scheme was proposed, which was based on the limited RF chains.First, an improved multiple signal classification algorithm was used to estimate the departure angle and arrival angle of the channel at the same time, and then a complex parallel deep neural network was proposed to estimate the path gain.Through simulation and comparison between the proposed scheme and other methods, the superiority of the proposed scheme is proved.